Development of Gamification-Based Digital Educational Game in Civic Education Learning on Rights and Obligations at Grade III Elementary Students - Vita Widyaningsih; Otib Satibi Hidayat; Evita Adnan (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
Students have a lot of developments rapidly ranging from language, emotions, and social at the elementary school level. This rapid development requires a teacher to be creative and active to optimize the students’ skills. The elementary students’ characteristics are happy learning through playing. Along with the development of advanced technology that grows rapidly, the researchers conducted research to produce gamification-based digital educational game products on Civic Education learning on rights and obligations learning material at grade III elementary students. The developed digital educational game utilizes gamification elements. The research method used was the research and development method with the ADDIE model from Cennamo, Abell, and Chung. The results of the expert validation test on this digital educational game get an average percentage score of 85.16%, which is in the very good category. The user trial results get a percentage of 100% from the group test and 99.3% from the field test in the very good category. Therefore, the gamification-based digital educational game product is suitable as media for Civic Education in the learning material of rights and obligations for grade III elementary students.